2014
DOI: 10.1155/2014/105420
|View full text |Cite
|
Sign up to set email alerts
|

The Beta-2-Adrenoreceptor Agonists, Formoterol and Indacaterol, but Not Salbutamol, Effectively Suppress the Reactivity of Human NeutrophilsIn Vitro

Abstract: The clinical relevance of the anti-inflammatory properties of beta-2 agonists remains contentious possibly due to differences in their molecular structures and agonist activities. The current study has compared the effects of 3 different categories of β2-agonists, namely, salbutamol (short-acting), formoterol (long-acting) and indacaterol (ultra-long-acting), at concentrations of 1–1000 nM, with human blood neutrophils in vitro. Neutrophils were activated with either N-formyl-L-methionyl-L-leucyl-L-phenylalani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…We observed effective inhibition of ROS production in all our 60 healthy donors with clinically relevant β 2 AR agonist concentrations . In concordance with previous studies, FORM was the most potent and SAL the least potent inhibitor of ROS production . The highly significant correlation of standardized pIC 50 values for all agonists demonstrated similar pharmacological responses toward treatment with different β 2 AR agonists in each individual proband.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed effective inhibition of ROS production in all our 60 healthy donors with clinically relevant β 2 AR agonist concentrations . In concordance with previous studies, FORM was the most potent and SAL the least potent inhibitor of ROS production . The highly significant correlation of standardized pIC 50 values for all agonists demonstrated similar pharmacological responses toward treatment with different β 2 AR agonists in each individual proband.…”
Section: Discussionsupporting
confidence: 90%
“…An alternative approach to explore effects of β 2 AR agonists is to test patient cells ex vivo for cellular adrenoresponses. Primary neutrophils represent a rather monomorphic, highly abundant, and easily accessible cell population for ex vivo testing of the β 2 AR effects . Neutrophils contribute to a plethora of inflammatory processes including asthma, and one of the most important defense mechanisms in neutrophils is the production of reactive oxygen species (ROS) .…”
mentioning
confidence: 99%
“…10 Furthermore, Anderson et al reported that formoterol suppressed the expression of adhesion molecules (CR3; CD11b/CD18) of neutrophils. 27 Taken together, we think that formoterol suppressed the eosinophil adhesion to ICAM-1 by suppressing the CD11b/CD18 expression on the eosinophil surface.…”
Section: Discussionmentioning
confidence: 67%
“…50 They also reported that cAMP accumulation is inversely correlated with eosinophil degranulation, and that the time course of cAMP accumulation closely paralleled that of inhibition of eosinophil degranulation. 50 As for neutrophils, formoterol increased cAMP more than salbutamol, 27,28 and suppressed neutrophil functions, including O 2 À generation, LTB 4 generation, and elastase release. 27,28 Furthermore, increased cAMP levels in neutrophils inhibited their adhesion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation